Leadership Therapy Inside the Mind of Microsoft - Rowley, Anna.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2007)
In Leadership Therapy, Microsoft consulting psychologist Anna Rowley draws on her twelve years of working with the top levels of Microsoft management, revealing the leadership skills that have helped the company maintain market dominance.
Keywords: Science; Science; Science, general; Electronic books